Extensive epidermoid cyst of the submental region - Estevam Rubens Utumi; Juliane Pirágine Araujo; Irineu Gregnanin Pedron; Frederico Yonezaki; Gustavo Grothe Machado; André Caroli Rocha (University of São Paulo, 2016)
Epidermoid cysts are malformations that are rarely observed in the submental region. Imaging has an important role in surgical planning according to the size and location of the cyst in relation to geniohyoid and mylohyoid muscles. This article reports the case of a 15-year-old female patient complaining of submental swelling. The differential diagnosis included infection, tumor, ranula, and abnormalities during embryonic development. The lesion was surgically excised using an extra-oral approach. The histopathological examination revealed a cyst wall lined with stratified squamous epithelium with the presence of several horny scales consistent with the diagnosis of an epidermoid cyst. No recurrences were found after 1 year of follow-up